Проблемы комплексной оценки инвестиционной привлекательности инновационных проектов - Усов, Максим Анатольевич; Сударкина, Светлана Петровна (International Academy of Theoretical & Applied Sciences, 2018)
В статье рассматривается проблема оценивания инвестиционной привлекательности проектов с учетом действия и силы влияния на проект и на его экономические характеристики стохастических, случайных факторов внешней и внутренней среды на базе экспертной оценки их влияния и расчета корректирующего коэффициента К кор.

The article deals with the problem of evaluating the investment attractiveness of projects taking into account the action and impact on the project and its economic characteristics of stochastic, random factors of external and internal environment on the basis of expert assessment of their impact and determination of the correction factor.
Problems of complex estimation of investment attractiveness of innovative projects
Keywords: инвестиционная привлекательность; экономическая эффективность; стохастические факторы; коэффициент корректирования; evaluation; investment attractiveness; economic efficiency; stochastic factors; correction factor; internal environment